Case Report: Morbihan disease treated with tofacitinib successfully - Li, Zi-Yun; Chi, Chao-Cheng; Cai, Sui-Qing (Frontiers in Immunology, 2023)
Introduction To date, there is no standard treatment for Morbihan disease. Several studies have reported that Morbihan disease responds well to systemic corticosteroids (prednisone and prednisolone), systemic antibiotics (tetracyclines), antihistamines (ketotifen) and surgical therapy (Lymphaticovenous anastomosis). To our knowledge, Tofacitinib, as a Janus-activated kinase (JAK) inhibitor, plays a vital role in the treatment of inflammatory and autoimmune disorders. Therefore, Tofacitinib may be a promising medical option for patients with Morbihan disease. Case Presentation The first case involves a 43-year-old Chinese man who presented a 12-month history of progressive painless swelling of the left upper eyelid. According to the skin biopsy, perivascular dermal edema with dilatation of lymphatic vessels and telangiectasia was observed, accompanied by mixed lymphocyte infiltrate, including histiocytes, plasma cells, and a few eosinophils. The second case involves a Chinese female patient who presented a 2-year history of progressive left-sided facial edema, which was eventually diagnosed as Morbihan disease. The skin biopsy revealed lymphocyte infiltration in the superficial vessels of dermis and some accessories. Based on patients’ clinical presentation, skin biopsy results, and exclusion of differential diagnoses such as systemic lupus erythematosus (SLE), they were diagnosed with Morbihan disease. They were both treated with Tofacitinib (5mg, po twice daily). Outcomes Patient 1 underwent a trial of Tofacitinib at a dosage of 5 mg twice daily for one month, with notable improvement. His edema and erythema present on the left face were alleviated. Patient 1 reduced the dosage of Tofacitinib by half (5mg, once daily) and continued using it for 5 months. During the 6-month follow-up, the facial erythema in the patient subsided, and there was a noticeable improvement in the swelling of the left eyelid compared to before. Patient 2, her lesions gradually improved after one-week treatment. She received a one-month treatment of Tofacitinib, and during the subsequent six-month follow-up, there was no evidence of eruption recurrence. Conclusion We present the first cases of two patients receiving short-term Tofacitinib as therapy for Morbihan disease and retrieving huge succession. Tofacitinib may be a promising oral alternative for patients with Morbihan disease. However, its safety and efficacy require further assessment through clinical trials.